2022
DOI: 10.3390/molecules27113586
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interfacial Reaction of Nano Al/CuO Energetic Films through Thermal Analysis and Ab Initio Molecular Dynamics Simulation

Abstract: The effect of the interface layer on energy release in nanoenergetic composite films is important and challenging for the utilization of energy. Nano Al/CuO composite films with different modulation periods were prepared by magnetron sputtering and tested by differential scanning calorimetry. With the increase in the modulation period of the nano Al/CuO energetic composite films, the interface layer contained in the energetic composite film decreased meaningfully, increasing the total heat release meaningfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Increasing the interfacial contact area and reducing the diffusion distance between reactants are key factors that can significantly enhance heterogeneous reactions. To achieve this, recent research has demonstrated the use of layered nano-interfaces, comprising densely packed nano-components, [23][24][25]. This innovative approach has proven to be more effective in accelerating flame propagation compared to uniformly distributed nano-components.…”
Section: Phonon Wave Excitation In Multilayered Nano-interfaces: Expl...mentioning
confidence: 99%
“…Increasing the interfacial contact area and reducing the diffusion distance between reactants are key factors that can significantly enhance heterogeneous reactions. To achieve this, recent research has demonstrated the use of layered nano-interfaces, comprising densely packed nano-components, [23][24][25]. This innovative approach has proven to be more effective in accelerating flame propagation compared to uniformly distributed nano-components.…”
Section: Phonon Wave Excitation In Multilayered Nano-interfaces: Expl...mentioning
confidence: 99%